Pelvic CT in addition to MRI to differentiate between rectal and sigmoid cancer on imaging using the sigmoid take-off as a landmark. (February 2023) - Bogveradze, Nino; Maas, Monique; el Khababi, Najim; Schurink, Niels W; Lahaye, Max J; Bakers, Frans CH; Tanis, Pieter J; Kusters, Miranda; Beets, Geerard L; Beets-Tan, Regina GH; Lambregts, Doenja MJ
Background: The sigmoid take-off (STO) is a recently established landmark to discern rectal from sigmoid cancer on imaging. STO-assessment can be challenging on magnetic resonance imaging (MRI) due to varying axial planes. Purpose: To establish the benefit of using computed tomography (CT; with consistent axial planes), in addition to MRI, to anatomically classify rectal versus sigmoid cancer using the STO. Material and Methods: A senior and junior radiologist retrospectively classified 40 patients with rectal/rectosigmoid cancers using the STO, first on MRI-only (sagittal and oblique-axial views) and then using a combination of MRI and axial CT. Tumors were classified as rectal/rectosigmoid/sigmoid (according to published STO definitions) and then dichotomized into rectal versus sigmoid. Diagnostic confidence was documented using a 5-point scale. Results: Adding CT resulted in a change in anatomical tumor classification in 4/40 cases (10%) for the junior reader and in 6/40 cases (15%) for the senior reader. Diagnostic confidence increased significantly after adding CT for the junior reader (mean score 3.85 vs. 4.27; P  < 0.001); confidence of the senior reader was not affected (4.28 vs. 4.25; P  = 0.80). Inter-observer agreement was similarly good for MRI only (κ=0.77) and MRI + CT (κ=0.76). Readers reached consensus on the classification of rectal versus sigmoid cancer in 78%–85% of cases. Conclusion: Availability of a consistent axial imaging plane – in the case of this study provided by CT – in addition to a standard MRI protocol with sagittal and oblique-axial imaging views can be helpful to more confidently localize tumors using the STO as a landmark, especially for more junior readers.